The Influence of Budget Participation and Information Technology on Employee Performance at the Majene Regency Maritime and Fisheries Service - Rusli, Rusli; Taufik, Taufik Hidayat B Tahawa; Ansari, Muhammad Ihsan Ansari (Kirana Publisher (KNPub), 2024)
The aim of this research is to determine the effect of budget participation and information technology on employee performance at the Majene Regency Maritime and Fisheries Service Office. Using the SPSS method, there were 45 respondents used as samples in this research, namely employees of the Majene Regency Maritime and Fisheries Service. The type of data used in this research is primary data. The data collection technique was carried out by distributing questionnaires to the research sample. Analysis of the t test, f test, and R2 test were used to test this research. The results of this research show that budget participation has a positive and significant effect on employee performance, information technology has a positive and significant effect on employee performance, budget participation and information technology together have a positive and significant effect on employee performance at the District Maritime and Fisheries Service Office Majene